Changes in Gallbladder Contractile Function and its Influencing Factors After Minimally Invasive Gallbladder-Preserving Surgery for Cholecystitis With Incarcerated Gallstones - Ai, Xiang-Nan; Wang, Teng-Fei; Zhang, Qiang; Ouyang, Cai-Guo; Wu, Zhen-Yu (Frontiers in Surgery, 2022)
Background: Cholecystitis with incarcerated gallstones (CIG) is a type of acute abdomen in the field of hepatobiliary surgery. Whether gallbladder-preserving surgery (GPS) can be performed to treat it, however, depends on the improvement of gallbladder contractile function. The present study aimed to investigate the changes in gallbladder contractile function and its influencing factors after minimally invasive GPS for CIG. Methods: A total of 95 patients with CIG treated in the Aerospace Center Hospital between May 2017 and May 2019 were enrolled as the study subjects. All patients received minimally invasive GPS. The patients’ operation-related conditions (including stone removal success rate, duration of surgery, intraoperative blood loss, etc.), changes in gallbladder contractile function, and influencing factors of GPS were analyzed. Results: Among the 95 patients included in the study, the success rate of stone removal was 100%, the duration of surgery was 76.0 ± 26.5 min, and the intraoperative blood loss was 10.17 ± 4.43 ml. The rate of good gallbladder contractile function at one and two years after surgery was significantly higher than before surgery (P < 0.05). Age, duration of surgery, stone recurrence, and diabetes were the independent risk factors for postoperative gallbladder contractile function (P < 0.05). Conclusion: Minimally invasive GPS for patients with CIG has a good curative effect. The changes in gallbladder contractile function after the surgery are influenced by many factors.